1987
DOI: 10.1002/art.1780300503
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte fc receptor function in rheumatoid arthritis. enhanced cell‐binding of igg induced by rheumatoid factors

Abstract: Monocytes from 11 patients with rheumatoid arthritis and 10 control subjects were purified by countercurrent elutriation. Rheumatoid arthritis monocytes had more cell-associated IgG ( P < 0.001) and bound more 1251-labeled heat-aggregated IgG in vitro (P < 0.02) than did monocytes from control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…By up-regulating CD64 and binding more IgG, monocytes increase their ability to bind ICs (40). Similar observations have previously been made in RA (41).…”
Section: Discussionsupporting
confidence: 85%
“…By up-regulating CD64 and binding more IgG, monocytes increase their ability to bind ICs (40). Similar observations have previously been made in RA (41).…”
Section: Discussionsupporting
confidence: 85%
“…[17][18][19] In our study we found that monocytes from patients with RA bound significantly more IgG at 4°C, which reflects the number of Fc receptors. The increased binding of '25I labelled IgG aggregates to monocytes of patients with RA compared with that to control monocytes might also be due to the presence of cell bound rheumatoid factor.…”
Section: Discussionsupporting
confidence: 54%
“…One of the patients analyzed suffered from severe erosive RA, but had no detectable rheumatoid factors or immune complexes (Clq binding and polyethylene glycol precipitation assay). Thus, at least in this patient it appears unlikely that these humoral factors are by themselves responsible for monocyte activation, which otherwise has been well substantiated (6). In a regular activation pathway, e.g., in infectious disease situations (45,46), monocytes receive their stimulatory signals from T cells.…”
Section: Discussionmentioning
confidence: 58%
“…There were striking differences between these two monocyte populations. Cells obtained from the first leukapheresis constitutively released large amounts of prostaglandin E2 (PGE2), neopterin, interleukin 1,6 (IL-1I#) and tumor necrosis factor-a (TNF-a). In particular, IL-1jB and neopterin production were further enhanced by stimulation with either interferon-'y (IFN-"y) or TNF-a without a synergistic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation